The Effects of Gamified Platforms on Enhancing Learners’ Ambition - Alrashedi , Nashmi Turaikhim; Alsulami, Salman Matar Hameed; Flatah, Ahmed Ibrahim; Najmi , Ali Hassan; Alhalafawy , Waleed Salim (Journal of Ecohumanism, 2024)
Gamification represents a novel technological approach that significantly enhances learners' motivation and ambition to advance in their educational pursuits. Gamification represents a significant tool in the advancement of digital platforms and learning management systems. Ambition represents a significant variable within the field of positive psychology, and the enhancement of its indicators has emerged as a crucial requirement for learners in today's context. A significant lack of research exists regarding the effects of gamification. This study investigates the influence of gamification on ambition. The Quasi-Experimental Approach was employed to analyse the differences between the first experimental group utilising gamified platforms (G1-Gamified Platforms) and the second experimental group engaging with the same platform devoid of gamification (G1-Non-gamified Platforms). The sample for this study comprised (80) ninth-grade students from Madinah, who were randomly assigned to the two groups involved in the investigation. A scale for ambition was created, encompassing four dimensions: optimism, goal-setting ability, acceptance of novelty, and resistance to failure and frustration, comprising a total of 35 items. The findings indicated that gamified platforms offer a distinct advantage over their non-gamified counterparts in fostering ambition. The impact of gamification elements on enhancing ambition among students across various educational levels calls for further exploration. The exploration of digital platforms and their integration of gamification strategies reveals a significant relationship with user ambition. This study aims to analyse how these elements interact and influence user engagement and motivation within various contexts.